2022
DOI: 10.1186/s12891-022-05089-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of the 95-degree angled blade plate with biological and mechanical augmentation to treat proximal femur non-unions: a case series

Abstract: Background Intertrochanteric and subtrochanteric non-union are rare but challenging complications. In the present study, we investigate the use of a 95° blade, in association with biological and mechanical augmentation, in the management of intertrochanteric and subtrochanteric femoral non-unions. Methods Between October 2015 and February 2021, a retrospective cohort study was conducted at our institution to investigate the use of a 95° blade, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
2
5
1
Order By: Relevance
“…The functional results of this study demonstrated statistically significant differences regarding the Harris Hip Score with higher values in the nail group compared with the blade plate group. This is in line with recent studies reporting that the Harris Hip Score demonstrated good results for both treatment concepts but indicating that cephalomedullary nailing was superior compared with extramedullary fixation methods [21,37].…”
Section: Discussionsupporting
confidence: 91%
“…The functional results of this study demonstrated statistically significant differences regarding the Harris Hip Score with higher values in the nail group compared with the blade plate group. This is in line with recent studies reporting that the Harris Hip Score demonstrated good results for both treatment concepts but indicating that cephalomedullary nailing was superior compared with extramedullary fixation methods [21,37].…”
Section: Discussionsupporting
confidence: 91%
“…As mentioned, the subtrochanteric region vasculature is precarious and could lead to delayed fracture consolidation, or non-union even in the latest reports on using IMN (7 -20%) [41]. However, for such complications, fixed-angle blade plates offer a reliable option for revision surgery with a high union rate [42]. It allows the removal of soft tissue interposition at the fracture interval, correction of malalignment, and addition of graft augmentation and compression.…”
Section: No Ideal Subtrochanteric Classification Systemmentioning
confidence: 99%
“…It allows the removal of soft tissue interposition at the fracture interval, correction of malalignment, and addition of graft augmentation and compression. A recent intertrochanteric and subtrochanteric nonunion management literature review of 289 cases found that 65.7% of them were treated with a blade plate (61.6% were 95-degree angle), and the union rate ranged from 91 -100% [42].…”
Section: No Ideal Subtrochanteric Classification Systemmentioning
confidence: 99%
“…Therefore, at present, Angle plates are not used as the first choice for the first surgical treatment of subtrochanteric fractures, and are often used in revision surgery for non-union of subtrochanteric fractures. Vicenti [7] et al used 95-degree Angle plates to treat 15 patients with intertrochanteric and subtrochanteric fractures after nonunion. A follow-up of 6 months showed a high rate of postoperative fracture union, a low incidence of complications, and a good clinical outcome.…”
Section: ° Angle Platesmentioning
confidence: 99%